Daya Antibakteri Kombinasi Kitosan Cangkang Udang Putih (Litopenaeus vannamei) dan Siprofloksasin terhadap Salmonella typhi (Antibacterial Activity of Combination of White Shrimp (Litopenaeus vannamei) Shells Chitosan and Ciprofloxacin against Salmonella - Sarah Marsa Tamimi; Dini Agustina; Cicih Komariah (Pustaka Kesehatan, 2017)
yphoid fever is an acute infectious disease in the intestinal tract caused by Salmonella typhi. The prevalence of typhoid fever in Indonesia in 2013 was 81% per 100,000 population. Ciprofloxacin is a large-spectrum antibiotics, but in some countries ciprofloxacin has been known to be resistant to S. typhi. Therefore, other methods are needed to improve the effectiveness of ciprofloxacin by combining with chitosan. Chitosan is a polysaccharide which known to be effective in some positive and negative Gram bacteria and able to overcome the resistance of some antibiotics. The research objective was to determine the effect of antibacterial and Minimum Inhibitory Concentration (MIC) of the combination of Litopenaeus vannamei chitosan and ciprofloxacin against S. typhi. The method used to obtain the value of the MIC was microdilution method with quasy-experimental research design and posttest only control group design. MIC which already been obtained then used to find the Fractional Inhibitory Concentration Index (FICI) using a checkerboard test to interpret the effect of the combination. The MIC combination showed different results in each repetition that chitosan: 15.63 to 62.5 µg/mL and ciprofloxacin from 0.03 to 0.5 µg/mL and known to have a smaller value than the MIC single. While the value of FICI from 5 repetitions was 0.476. So, it could be concluded that the combination of chitosan and ciprofloxacin has an antibacterial effect on S. typhi and have a synergistic combination effect. Keywords: Salmonella typhi, chitosan, ciprofloxacin, microdilution method, checkerboard test.